Alih Profesi Menjadi Penjual Minuman Keras (MIRAS) Ilegal Pasca Pandemi Covid-19 - Moh. Y. Un. Mayalibit; Muhamad Yusuf; Pahri Pahri; Rachmad Surya Muhandy (Jayapangus Press, 2022)
This study aims to determine the change in the profession of citizens to become sellers of illegal liquor in post the Covid-19 pandemic on Jalan Baru Abepura, Jayapura City. This is qualitative research with the paradigm of social phenomenology, by conducting observations and interviews, using flow chart analysis techniques from Milles B. Huberman. The results of the study: Sales of the liquor increased on holidays, Christmas and New Year. The rise of liquor sellers caused by the Covid-19 Pandemic. This happens because community activities have an impact on the lack of income in people's lives so that it is a way to find other business opportunities. The sale of liquor is carried out by immigrants from outside Papua who inhabit the area. They know each other and are managed together. The increase in the consumption of liquor has caused unrest among the people of the city of Jayapura. Unscrupulous officers unilaterally forced liquor sellers on the roadside to ask for money as a condition that must be met to avoid raids. Unscrupulous officials give the existence of raids on illegal liquor sellers so that they can continue to operate through agreements and agreements, so that raid officers can be identified, and sellers can carry out their trade without having to be with informed officers.